The Relationship between Transformational Leadership of School Administrators and School Effectiveness under the Secondary Educational Service Area Office Phra Nakhon Si Ayutthaya - Kreephat, Kritlada; กลิ่นเกษร อุษาพร (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
The purposes of this research were 1) to study the level of transformational leadership of school administrators 2) to study the level of school effectiveness and 3) to study the relationship between transformational leadership of school administrators and school effectiveness under the Secondary Educational Service Area Office Phra Nakhon Si Ayutthaya. The sample consisted of 308 teachers, determined by Yamane’s formula (1973) and selected through stratified and simple random sampling. The research instrument was a five-point rating scale questionnaire with an Index of Item-Objective Congruence (IOC) ranging from 0.80 to 1.00 and a reliability coefficient of 0.987. Data were analyzed using frequency, percentage, mean, standard deviation, and Pearson’s product–moment correlation coefficient. The research results found that : • The transformational leadership of school administrators, both overall and in each dimension, was at a high level. The dimension with the highest mean score was intellectual stimulation, followed by inspirational motivation, while individualized consideration showed the lowest mean score. • The effectiveness of schools, both overall and in each aspect, was also at a high level. The aspect with the highest mean score was the ability to develop students’ positive attitudes, followed by the ability to adapt and develop the school, whereas the ability to solve internal school problems had the lowest mean score. • The relationship between the transformational leadership of school administrators and school effectiveness was positively correlated at a high level (r = .858), with statistical significance at the .01 level.